Regression Analysis for the Identification of RAPD Markers Linked To Drought Tolerance in Sorghum - Paramita Cahyaningrum; T. Taryono; Anto Rimbawanto (Universitas Gadjah Mada, 2012)
Sorghum (Sorghum bicolor) can actually withstand in dry or drought condition better than other crops,therefore it can be grown at different agroclimatic conditions and its product can be used for different purposessuch as food, feed and industrial raw material. However at severe condition, the productivity will also dropdrastically. The aim of this research was to identify RAPD marker linked to the drought tolerance. In thisresearch, varieties of sorghum used as research materials were Durra, Zhengzu, the mutants of Durra andZhengzu (from 300 Gy gamma radiation) B-100 and Zh-30, and the F2 seeds from Zh-30 x B-100 and B-100 xZh-30. Drought screening was carried out using 0.3 % KI during sorghum vegetative stage. DNA extractionwas done using a modified CTAB method. PCR was carried out for RAPD analysis. PCR amplification productswere scored and analyzed using SAS program. The result showed that potassium iodide can be used fordrought screening during the vegetative stage and regression analysis using the logistic method can be usedto identify RAPD markers that is linked to drought tolerance in sorghum. The logistic analysis showed thatband A8-480 was linked to drought tolerance in sorghum.